Kinematics of landslide estimated by repeated GPS measurements in the Avcilar region of Istanbul, Turkey - Dogan, Ugur; Oz, Deniz; Ergintav, Semih (SPRINGER, 2013)
The aim of this study is to analyze the spatial and temporal behavior of the landslide located in Avcilar region which is situated between Kucukcekmece and Buyukcekmece Lakes in the north-west of Marmara region, Turkey. A network consisting of 10 sites has been surveyed four times from November 2007 to May 2009 using Global Positioning System (GPS). The deformation analysis has been applied to determine the landslide movement parameters of the sites using GPS measurements of the four epochs. The reliable and high precision deformation rates are presented in terms of displacement vectors, velocity vectors and changes of accumulated strain. Landslides of the region are characterized from a regional GPS network. Each site has statistically different temporal behavior and significant relative motions and the region has irregular landslide movements.
Keywords: landslide; Marmara region; GPS; deformation analysis; POSTSEISMIC DEFORMATION; IZMIT EARTHQUAKE; FIELD; AREA; Geochemistry & Geophysics